Intraventricular hemorrhage in preterm babies - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2020)
Germinal matrix-intraventricular hemorrhage (GM-IVH) is a major complication of prematurity and inversely associated with gestational age and birth weight. The hemorrhage originates from the germinal matrix with an immature capillary bed where vascularization is intense and active cell proliferation is high. It occurs in around 20% of very low-birth-weight preterm neonates. Germinal matrix-intraventricular hemorrhage is less common in females, the black race, and with antenatal steroid use, but is more common in the presence of mechanical ventilation, respiratory distress, pulmonary bleeding, pneumothorax, chorioamnionitis, asphyxia, and sepsis. Ultrasonography is the diagnostic tool of choice for intraventricular hemorrhage and its complications. Approximately 25-50% of the germinal matrix-intraventricular hemorrhage cases are asymptomatic and diagnosed during routine screening. These cases are usually patients with low-grade hemorrhage. Neurologic findings are prominent in severe intraventricular hemorrhage cases. The major complications of the germinal matrix-intraventricular hemorrhage in preterm babies are periventricular hemorrhagic infarction, posthemorrhagic ventricular dilatation, periventricular leukomalacia, and cerebellar hemorrhage. It is an important cause of mortality and morbidity. The management of hemodynamics and ventilation of patients, appropriate follow-up, and early diagnosis and treatment can minimize morbidity. Prognosis in intraventricular hemorrhage is related to the severity of bleeding, parenchymal damage, and the presence of seizures and shunt surgery. The main determinant of prognosis is periventricular hemorrhagic infarction and its severity. Moderate-severe intraventricular hemorrhage can cause posthemorrhagic hydrocephalus, cerebral palsy, and mental retardation. Even mild germinal matrix-intraventricular hemorrhage can result in developmental disorders. Long-term problems such as neurodevelopmental disorders and cerebral palsy are as important as short-term problems. Improving the quality of life of these babies should be aimed through appropriate treatment and follow-up. In this review, intraventricular hemorrhage and complications are discussed.
Keywords: Intraventricular hemorrhage; posthemorrhagic ventricular dilatation; preterm; POSTHEMORRHAGIC HYDROCEPHALUS; VENTRICULAR DILATATION; INFANTS BORN; BIRTH; POLYMORPHISMS; RISK